Problem Solving Ability Viewed from Students’ Cognitive Style on Brain-Based Learning Model Based on Self-Assessment - Uji, La Toni; Asikin, Mohammd; Mulyono, Mulyono (Universitas Negeri Semarang, 2021)
This study aimed to describe the ability of problem solving based on students' cognitive styles. This study used a mixed method with explanatory sequential design. The population was the students of XI-IPS class from SMA 4 Buru in academic year 2019/2020. The subjects in this study were students of class XI-IPS 1 which were selected based on cognitive style analysis using the Group Embedded Figure Test (GEFT). Data collection techniques used observation, tests and interviews. The results showed that the students 'mathematical problem solving abilities in the cognitive style category had different mastery of indicators in solving students' mathematical problems. This difference does not depend on the cognitive style category of students, yet because of student learning activities.